Perceived leadership behaviours of school managers and their effects in the implementation of the annual national assessments - Kwatubana, Siphokazi; Ntekane, Abram (Penerbit Universiti Kebangsaan Malaysia, 2021)
Research indicates that to improve academic performance, school managers should exert leadership in the implementation of national assessments. This article explores leadership behaviour as a factor that either affords or constrains the effective implementation of the Annual National Assessments (ANAs) in schools. Fiedler’s contingency theory of leadership effectiveness was used as a framework to explore the leadership conduct of school managers in three South African schools. This was a qualitative study, approached from a realistic, interpretivist perspective. The study population consisted of school managers and teachers who taught subjects that were evaluated through the Annual National Assessments. The findings were drawn from a case study design, and the data were organised according to Fiedler’s two forces of leadership effectiveness: leadership style and the situational favourableness. The findings show that although the participants mostly favoured Fiedler’s task-orientated leadership style, its effectiveness was hindered by the adverse contexts in which the ANAs were administered. The findings of this study contribute to school leadership and school improvement literature and should inform discussions on how to prepare school managers for the soon to be implemented National Integrated Assessment Framework (NIAF). These results direct the attention of assessment policymakers and facilitators towards conditions in schools that describe its capacity for change and improvement especially regarding annual assessments.